ANDROID DATA SECURITY USING CRYPTOGRAPHIC ALGORITHM COMBINATIONS - Lia Hananto , April; Priyatna, Bayu; Rosita, Ai (International Journal of Psychosocial Rehabilitation, 2020)
Android is a platform that is very vulnerable to hacked by bad people to steal users’ data intentionally or unintentionally [1]. To deal with data disturbances it is necessary to use cryptography [2], one of which is Playfair Chipper. Playfair’s cryptographic algorithms are currently being developed with various types of matrix table modifications, ranging from changes in matrix size, or changes in the encryption process steps. The results of applying the Playfair combination and modification algorithm with the Linear Feedback Ship Register (LFSR) for securing data on the Android platform. Testing the application of the results of the Playfair algorithm modification using the Avalanche Effect can be concluded that the resulting ciphertext has a high complexity.